2017
DOI: 10.1186/s12864-017-3970-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fasciclin-like arabinogalactan proteins in textile hemp (Cannabis sativa L.): in silico analyses and gene expression patterns in different tissues

Abstract: BackgroundThe fasciclin-like arabinogalactan proteins (FLAs) belong to the arabinogalactan protein (AGP) superfamily and are known to play different physiological roles in plants. This class of proteins was shown to participate in plant growth, development, defense against abiotic stresses and, notably, cell wall biosynthesis. Although some studies are available on the characterization of FLA genes from different species, both woody and herbaceous, no detailed information is available on the FLA family of text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 46 publications
1
45
1
Order By: Relevance
“…In hemp, a motif recognized by MYB3 was found in the promoter sequence of the FASCICLIN-LIKE ARABINOGALACTAN (FLA) genes that are highly expressed in mature phloem fibers. Those FLAs may be under a MYB3-driven regulatory circuit determining bast fiber hypolignification [51].…”
Section: R2r3 Mybs the Gatekeepers Of Scw Formation And Lignificationmentioning
confidence: 99%
“…In hemp, a motif recognized by MYB3 was found in the promoter sequence of the FASCICLIN-LIKE ARABINOGALACTAN (FLA) genes that are highly expressed in mature phloem fibers. Those FLAs may be under a MYB3-driven regulatory circuit determining bast fiber hypolignification [51].…”
Section: R2r3 Mybs the Gatekeepers Of Scw Formation And Lignificationmentioning
confidence: 99%
“…FLA families have been identi ed and characterized in several plants including Arabidopsis [8], rice [9,10], wheat [10], poplar [11], cotton [12], Chinese cabbage [13], Eucalyptus grandis [14] and textile hemp [15]. In this study, we identi ed 38 FLAs in N. benthamiana and found that their structural domains were conserved by studying phylogenetic trees, gene structure and conserved motifs (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…So far, the FLA family members have been identi ed in several plant species. 21 FLAs have been identi ed in Arabidopsis thaliana [8], 27 in rice (Oryza sativa) [9,10], 34 in wheat (Triticum aestivum) [10], 35 in poplar (Populus trichocarpa) [11], 19 in cotton (Gossypium hirsutum) [12], 33 in Chinese cabbage (Brassica rapa) [13], 18 in Eucalyptus grandis [14] and 23 in textile hemp (Cannabis sativa) [15]. FLAs are cell wall structural glycoproteins that mediate cellulose deposition and cell wall development.…”
Section: Introductionmentioning
confidence: 99%
“…The snap point was determined as previously described [9]. Each segment was separated in cortical tissues (harbouring the bast fibres, annotated as OUT) and core tissues (containing the xylem with its associated fibres and the pith, annotated as IN), according to [9,11]. To avoid excessive variation in gene expression, a segment of ca.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%